Analisis Total Productive Maintenance (TPM) pada Mesin Labelling Menggunakan Overall Equipment Efectiveness di PT. G - Hidayatullah, Revanda; Nurkhaerani, Fatma (Fakultas Teknik Universitas Tulang Bawang, 2026)
The technology used in a company will continue to advance with time. The technology frequently used involves reliable production machines for smooth production processes. Therefore, machines that play a crucial role in the production process must be well-maintained. Inaccuracies in quality checks on goods to be sold in the market will result in complaints or losses for the company from the released products. Such losses include insufficient attention to checking the quality of products and machines, leading to imperfections in surface evenness and hindering the process. Total Productive Maintenance (TPM) is a maintenance approach that optimizes machine efficiency, reduces breakdowns, and includes autonomous maintenance performed by machine operators. Based on data from weeks 1 to 4 in March 2024, it can be concluded that calculations using the TPM method resulted in an OEE value of 94%, indicating that the productivity and efficiency level of machines or equipment at PT. G has surpassed world-class standards and is near-perfect. Factors that can be improved to achieve an OEE value of 100% are Availability and Rate of Quality. Keywords: Overall Efectiveness Equipment, Production, Total Productive Maintenance